Knowledge in cities - Todd Gabe; Jaison R. Abel; Adrienne Ross; Kevin Stolarick (Federal Reserve Bank of New York, 2010)
This study identifies clusters of U.S. and Canadian metropolitan areas with similar knowledge traits. These groups - ranging from Making Regions, characterized by knowledge about manufacturing, to Thinking Regions, noted for knowledge about the arts, humanities, information technology, and commerce - can be used by analysts and policymakers for the purposes of regional benchmarking or comparing the types of programs and infrastructure available to support closely related economic activities. In addition these knowledge-based clusters help explain the types of regions that have levels of economic development that exceed, or fall short of, other places with similar amounts of college attainment. Regression results show that Engineering, Enterprising, and Building Regions are associated with higher levels of productivity and earnings per capita, while Teaching, Understanding, Working, and Comforting Regions have lower levels of economic development.
Keywords: R11; O18; J24; 330; Knowledge; occupations; economic development